2021
DOI: 10.3389/fchem.2021.687996
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Enables Tunable Molecular Interaction and Photovoltaic Performance in Non-Fullerene Solar Cells Based on Ester-Substituted Polythiophene

Abstract: Owing to the advantages of low synthetic cost and high scalability of synthesis, polythiophene and its derivatives (PTs) have been of interest in the community of organic photovoltaics (OPVs). Nevertheless, the typical efficiency of PT based photovoltaic devices reported so far is much lower than those of the prevailing push-pull type conjugated polymer donors. Recent studies have underscored that the excessively low miscibility between PT and nonfullerene acceptor is the major reason accounting for the unfavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This side chain approach to moderately enhance the D/A interactions could be appealing because it would not sacrifice the V OC of devices, which often happened in halogenated SMAs for the enhancement of D/A interactions. [ 55 ]…”
Section: Resultsmentioning
confidence: 99%
“…This side chain approach to moderately enhance the D/A interactions could be appealing because it would not sacrifice the V OC of devices, which often happened in halogenated SMAs for the enhancement of D/A interactions. [ 55 ]…”
Section: Resultsmentioning
confidence: 99%
“…According to a previous study, reasonably miscible D/A blends are preferred to balance exciton dissociation and charge transport, which occur in D/A interfaces and connected pure phases, respectively. [48,49] The relatively smaller binding energies between PM6-and LA-series acceptors did not affect the exciton dissociation capacity, which had reasonable dissociation probabilities (η diss ) of over 99% (Figure S15, Supporting Information). Instead, the moderate D/A interactions and restrained miscibility help refine the phase separation with larger CCL values.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorinated conjugated polymers or molecular acceptors could enhance the PCE of OPV devices. , Donors and acceptors incorporating fluoro-substitution may be used to improve the PCE of devices because of their corresponding electron-deficient natures, thereby the frontier molecular orbital (FMO) energy of donors can be tuned. Acceptors incorporating fluoro-substituted moieties could exhibit enhanced compatibility with donors; thus, phase morphology parameters such as the fibril structure, carrier mobility, and charge extraction can be improved. , To the best of our knowledge, some oligomeric fused-ring electron acceptors containing more than one fused-ring unit exhibited an improved device efficiency with electron-deficient bridges, and some literatures reported that fluorination has a beneficial effect on the morphology, miscibility, and crystallinity of the active layer. Inspired by the semiconducting self-assembled nanofibers from photostable octafluorinated bisanthene derivatives and enhancement of PCE by a σ-hole solid additive, 1,4-diiodotetrafluorobenzene, we designed a molecular acceptor by tethering the fused-ring core structure of indacenodithienothiophene ( IDTT ) with a p -tetrafluorophenylene divinylene moiety. In this system, the electron-deficient p -tetrafluorophenylene divinylene ( FB ) moiety served as an electron-deficient core (A′), in which two IDTT donors were tethered and end-capped with two electron-withdrawing 2-(5,6-dichloro-3-oxo-2,3-dihydro-1 H -inden-1-ylidene)­malononitriles ( ClIN ); thus, the conjugation and tethering of IDTT with an A′ unit enabled the tuning of the FMO energy levels.…”
Section: Introductionmentioning
confidence: 99%